RELEVANSI MODERASI BERAGAMA LUKMAN HAKIM SAIFUDDIN DENGAN MASYARAKAT INDONESIA (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2024)
Religious moderation is something that is very important and should be a guideline for the lives of multicultural Indonesian people because diversity in Indonesia is a gift that we should be grateful for, not a problem. However, Indonesian people who are too fanatical about ethnicity, race, and culture cause problems that they consider small even though they affect the survival of many people. Lukman Hakim Saifuddin defines religious moderation as a middle way in the diversity of Indonesian society in fighting extreme attitudes. This research is a type of research that uses a qualitative approach or library research with a descriptive analysis method. The data analysis used is content analysis. Primary data in this study comes from a book written by Lukman Hakim Saifuddin "Religious Moderation". Then for secondary data comes from other books that are in accordance with the discussion, journals, theses, theses, and various other library sources that are in accordance with the research. The results of this study show the relevance of religious moderation from Lukman Hakim Saifuddin's perspective in Indonesia. Lukman Hakim Saifuddin said that if a moderate attitude has been instilled in every Indonesian society, life will run peacefully without conflict, and isn't this the kind of life that we always dream of? Every religion has teachings that require its followers to live peacefully, but many people misunderstand the teachings of their own religion.